WRITING THEORIES AND WRITING PEDAGOGIES - Ken Hyland (Universitas Katolik Indonesia Atma Jaya, 2008)
This paper explores the main approaches to understanding and teaching writing. Making a broad distinction between theories concerned with texts, with writers and with readers, I will show what each approach offers and neglects and what each means for teachers. The categorisation implies no rigid divisions, and, in fact the three approaches respond to, critique, and draw on each other in a variety of ways. I believe, however, this offers a useful way of comparing and evaluating the research each approach has produced and the pedagogic practices they have generated. Keywords: Teaching writing; Pedagogic practices; Approaches